SLOfit Lifelong: A model for leveraging citizen science to promote and maintain physical fitness and physical literacy across the lifespan - Jurak, Gregor; Morrison, Shawnda A.; Soric, Maroje; Leskošek, Bojan; Kovač, Marjeta; Ocvirk, Tjaša; Sember, Vedrana; Kramaršič, Jaka; Meh, Kaja; Potočnik, Žan Luca; Blagus, Rok; Markelj, Neja; et al. (Frontiers in Public Health, 2022)
SLOfit Lifelong is a public health initiative which was created to upgrade a well-established, national physical fitness surveillance system for Slovenian schoolchildren that has been collecting annual fitness and health data for over three decades. The ultimate objective of creating SLOfit Lifelong was to build a modern societal infrastructure with the capacity and ability to detect future causal associations between childhood physical fitness trends and future health outcomes based on the lifelong surveillance of one's own fitness status. By instilling citizens with an ambition to test, understand, and follow-up their own physical fitness and health status (including related health risk factors), this initiative provides the technical support and expert feedback needed to engender greater individual control over understanding (and thus modulating), one's own physical fitness status as they progress into older adulthood. This perspective paper details the extensive approach taken to devise appropriate fitness test batteries for adults and older adults which can also relate to the student version of the original SLOfit test database, including establishing criterion health risk zones and a public approach to establish this national, citizen-driven health feedback framework. Through its sophisticated online web applications, social media, print media, and outreach workshops, SLOfit Lifelong provides the expert support for public health engagement by fostering positive lifelong physical literacy experiences an individual can enjoy across their aging journey.